The Simplified Carbapenem Inactivation Method (sCIM) for Simple and Accurate Detection of Carbapenemase-Producing Gram-Negative Bacilli - Jing, Xiaopeng; Zhou, Huan; Min, Xiaochun; Zhang, Xing; Yang, Qing; Du, Shuaixian; Li, Yirong; Yu, Fangyou; Jia, Min; Zhan, Yu; Zeng, Yi; Yang, Bo; et al. (Frontiers in Microbiology, 2018)
This study reportedaimed to design a method, called the simplified carbapenem inactivation method (sCIM), for the simple and accurate detection of carbapenemase-producing gram-negative bacilli. This method is based on modified carbapenem inactivation method (mCIM) with improvement of experimental procedures: Instead of incubating the antibiotic disk in the organism culture media, organism to be test was smeared directly onto antibiotic disk. for simple and accurate detection of carbapenemase phenotypes. ForWe evaluatinged the sensitivity and specificity of the method, called the simplified carbapenem inactivation method (sCIM), for the detection of carbapenemase-producing gram-negative bacilli. A a total of 196 Enterobacteriaceae, 73 Acinetobacter baumannii, and 158 Pseudomonas aeruginosa isolates were collected. PCR was used to detect carbapenemase genes. Phenotypic evaluations were performed using both the sCIM and mCIM. PCR results showed that, of the 196 Enterobacteriaceae strains, 147 expressed the carbapenemase genes blaKPC-2 (58.5%), blaIMP-4 (21.8%), blaIMP-2 (2.0%), blaVIM-1 (6.1%), blaNDM-1 (10.2%) and blaOXA-48 (1.4%). sCIM results had high concordance with PCR results (99.5%) and mCIM results (100%) with the exception of one Klebsiella pneumoniae strain, which had an MIC for imipenem of 0.25 mg/L. PCR demonstrated that 53 of 73 A. baumannii isolates expressed the carbapenemase genes blaOXA-23 (98.1%) and blaVIM-2 (1.8%). sCIM and PCR results corresponded but all A. baumannii isolates were carbapenemase negative by mCIM. PCR demonstrated that 25 of 158 P. aeruginosa isolates expressed carbapenemase genes blaVIM-1 (52%), blaVIM-2 (8%), blaVIM-4 (36%) and blaIMP-4 (4%). sCIM results had high concordance with PCR results (100%) and mCIM results (99.4%) with the exception of one P. aeruginosa isolate that expressed the blaVIM-4 gene. sCIM offers specificity and sensitivity comparable to PCR but has the advantage of being more user-friendly. This method is suitable for routine use in most clinical microbiology laboratories for the detection of carbapenemase-producing gram-negative bacilli.